Esophagectomy in esophageal perforations: an analysis. Issue 1 (1st January 2016) - Abu-Daff, S.; Shamji, F.; Ivanovic, J.; Villeneuve, P. J.; Gilbert, S.; Maziak, D. E.; Sundaresan, R. S.; Seely, A. J. E.
Summary: This study aimed to study the factors that are associated with urgent esophagectomy for the treatment of esophageal perforations and the impact of this therapy. A retrospective review of all esophageal perforations treated at a tertiary care hospital from January 1984 to January 2012 was performed. Compiling demographics, cause and site of perforations, time to presentation, comorbidities, radiological tests, the length of perforation, the hemodynamic status of the patient, type of treatment required, and outcomes were performed. Univariate, multivariate, and Cox regression analyses were conducted. Of 127 cases of esophageal perforation, it was spontaneous in 44 (35%), iatrogenic in 53 (44%), foreign body ingestion in 22 (17%), and traumatic perforation in 7 (6%) cases. Overall, 85 of the 127 (67%) patients were managed operatively, 35 (27.6%) patients were treated conservatively, and 7 (6.3%) patients were treated by endoscopic stent placement. Of the 85 patients who were managed operatively, 21 (16.5%) required esophagectomies, 13 (15.3%) had esophagectomy with immediate reconstruction, 5 (5.9%) patients had esophagectomy followed by delayed reconstruction, and 3 (3.5%) patients failed primary repair and required an esophagectomy as a secondary definitive procedure. Multivariate analysis revealed that esophagectomy in esophageal perforations was associated with the presence of benign or malignant esophageal stricture ( P = 0.001) and a perforation >5 cm ( P = 0.001). Mortality was mainly associated with the presence of a benign or malignant esophageal stricture ( P = 0.04). The presence of pre-existing benign or malignant stricture or large perforation (>5 cm) is associated with the need for an urgent esophagectomy with or without immediate reconstruction. Performing esophagectomy was not found to be a significant prognosticator for mortality.